The effect of readiness on technology application and lecturer performance in private higher education - Saiman, Nur Nadiah; Mohd Daud, Norzaidi; Zulkifli, Nordayana (Universiti Teknologi Mara Selangor, 2024)
The purpose of this study is to investigate the effects of readiness on technology use and how it affects lecturer performance in private higher education institutions. Due to technology and digitalization, the increasing integration of digital tools and platforms in higher education will explore how technology influences teaching effectiveness and overall performance has become essential. The key variables in this research include the lecturer’s performance, technology application and technology readiness. A feasibility study was conducted, and several pieces of literature related to the effect of technology application on lecturer’s performance were analyzed. A quantity approach will be adopted utilizing a survey method to collect primary data from lecturers in private universities. This study provides significant insights into the relationship between technology readiness, the application of technology, and lecturer performance in private higher education institutions. The study contributes to the growing body of literature on educational technology and provides a framework for further research on this critical topic in the context of higher education. Moreover, this study highlights the importance of continuous professional development and training for lecturers to keep up with technological advancements and enhance training programs for technological proficiency in future.